Productivity and physiology of kale inoculated with entomopathogenic fungi of Amazon region to control caterpilla - Oliveira Gomes, Débora; Franciele Barreira de Melo , Naiane; da Costa Leite, Rubson; Henrique Santos Rodrigues, Flavio; Luiz Salgado de Castro, Gledson; Rodrigues Galvão, Jessivaldo; Gomes Viana, Rafael; Fátima Vieira Batista, Telma (Comunicata Scientiae, 2023)
The use of biological control agents such as entomopathogenic fungi is an alternative for the control of kale (Brassica oleracea L.) defoliating caterpillars. The objective was to investigate the efficacy of entomopathogenic fungi of Amazon region in the control of defoliating caterpillars in kale and their impacts on the physiological and agronomic responses of the crop. Field and greenhouse experiments were conducted in randomized block design and completely randomized design, respectively. The treatments consisted in the application of isolates of entomopathogenic fungi: Beauveria bassiana, Isaria sp., Metarhizium anisopliae and Trichoderma asperellum. The control treatment consisted of the application of an chemical insecticide based on deltamethrin.Variables referring to the development, yield and physiology of the plants were evaluated. Field results revealed that plants treated with the fungi B. bassiana, M. anisopliae and T. asperellum showed levels of severity, number of leaves and commercial yield that did not differ from the standard treatment; however, they showed a lower population density of the defoliating caterpillar complex. The application of the treatments with M. anisopliae and chemical insecticide showed better photosynthetic performance. In greenhouse, the fungus T. asperellum provided greater plant height and robustness index in relation to the treatment with chemical insecticide. The entomopathogenic fungi of Amazon region can be contributed to the integrated management of leaf defoliating caterpillars in kale. These microorganisms have similar efficiency with chemical insecticides, being ecologically and economically viable to mitigate the negative impacts caused by the systematic use of chemicals.